Evidencia empírica de la estructura de capital y el valor de las empresas que cotizan en la bolsa de valores de Lima, periodo-2015 - Villacorta Malqui, Manuel Alejandro (2017)
Does the capital structure impact the value of companies on the Lima Stock Exchange in the period 2015? The study sought to explain the influence of capital structure on the value of the company. The study is of a basic type, with a quantitative approach and an explanatory level. A non-experimental causal correlational transactional approach was used. The sample was 23 issuing companies from the Lima Stock Exchange, selected from a population of 58 using simple random sampling and data collection with content analysis and bibliographic records. The value of debt and equity positively affects the value of companies on the Lima Stock Exchange, while the cost of capital has a negative effect. There is a considerable high positive correlation r=0.787 and p=0.000 < α=0.05 was found, so the debt-equity composition affects the value of the company.